Performance of corrosion inhibitor with sand deposit in co2 environment - Abd Karim, M.A. (Asian Research Publishing Network, 2016)
The performance of corrosion inhibitor on API X65 carbon steel covered by sand deposit under CO2 environment is presented. The effect of corrosion inhibitor concentration on a constant sand deposit thickness was analyzed using Linear Polarization Resistance (LPR) electrochemical method. In addition, the effect of each element alone on corrosion behaviour was also studied for comparison purpose. The results indicated that both corrosion inhibitor and sand deposit could retard the corrosion rate either by working alone or exist together in a system. The overall performance of inhibitor with or without deposit is almost similar suggesting that the controlling factor for corrosion rate in this experiment was the rate of absorption towards the metal surface through sand deposit by corrosive species and inhibitor. Â©2006-2016 Asian Research Publishing Network (ARPN).